Divertikulární choroba tračníku - chirurgická léčba - Levý, M; Herdegen, P; Sutoris, K; Simša, J (Rozhledy v chirurgii, 2013)
INTRODUCTION: Surgical treatment, despite the rapid development of the numerous modern miniinvasive intervention techniques, remains essential in the treatment of complicated diverticular disease. AIM: The aim of this work is to summarize indications for surgical treatment in both acute and elective patients suffering from diverticular disease of the large bowel. METHODS: Review of the literature and recent findings concerning indications for surgical intervention in patients with diverticulosis of the colon. CONCLUSION: The article describes indications, types of procedures, techniques and postoperative care in patients undergoing surgical intervention for diverticular disease.
Keywords: chirurgie trávicího traktu; Diverticulosis, Colonic; kolon; Elective Surgical Procedures; Humans; divertikl tlustého střeva; elektivní chirurgické výkony; divertikulóza tlustého střeva; Colon; lidé; Digestive System Surgical Procedures; Diverticulum, Colon